Community Service Through Real Work Lectures (KKN) in Sungai Ular Village, Langkat Regency - Lubis, Annisa Athaya Putri; Karim, Pangulu Abdul; Hasanah, Aulia Nurul; Nasution, Elna; Rachman, Tengku Muhammad Rafly (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The Community Service Program (KKN) in Sungai Ular Village, Secanggang District, Langkat Regency, aims to develop community potential through three main focuses: religious moderation, empowerment of digital technology-based MSMEs, and stunting prevention. Through a Participatory Action Research (PAR) approach, KKN activities involve the community directly in the process of social and economic improvement. The religious moderation program has succeeded in deepening understanding of religion, increasing tolerance, and strengthening relations between religious communities through activities such as Maghrib Koran Recitation, Wirit for Mothers, and Wirit for Youth. Empowerment of MSMEs, especially in the palm sugar sector, is carried out by providing digital marketing training and promotional support through e-commerce platforms to expand markets and increase income. The stunting prevention program provides education to the public regarding the importance of balanced nutrition, reproductive health, and the impact of early marriage on stunting. The results of implementing this KKN show increased community awareness and sustainability in local economic development and public health, which has the potential to reduce the prevalence of stunting and improve the quality of life in Sungai Ular Village.